Advanced optical trapping by complex beam shaping. Issue 6 (7th January 2013) - Woerdemann, Mike; Alpmann, Christina; Esseling, Michael; Denz, Cornelia
<x xml:space="preserve">Abstract</x> Optical tweezers, a simple and robust implementation of optical micromanipulation technologies, have become a standard tool in biological, medical and physics research laboratories. Recently, with the utilization of holographic beam shaping techniques, more sophisticated trapping configurations have been realized to overcome current challenges in applications. Holographically generated higher‐order light modes, for example, can induce highly structured and ordered three‐dimensional optical potential landscapes with promising applications in optically guided assembly, transfer of orbital angular momentum, or acceleration of particles along defined trajectories. The non‐diffracting property of particular light modes enables the optical manipulation in multiple planes or the creation of axially extended particle structures. Alongside with these concepts which rely on direct interaction of the light field with particles, two promising adjacent approaches tackle fundamental limitations by utilizing non‐optical forces which are, however, induced by optical light fields. Optoelectronic tweezers take advantage of dielectrophoretic forces for adaptive and flexible, massively parallel trapping. Photophoretic trapping makes use of thermal forces and by this means is perfectly suited for trapping absorbing particles. Hence the possibility to tailor light fields holographically, combined with the complementary dielectrophoretic and photophoretic trapping provides a holistic approach to the majority of optical micromanipulation scenarios. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>